Resource Allocation for Image Transmission Using Adaptive Semantic and Bit Communication - Li, Peixuan; Wang, Yichen; Tang, Xiao; Liu, Moqi; Liu, Haotian; Cheng, Julian (IEEE transactions on wireless communications, 2025)
Semantic communication is an emerging technology to improve the communication efficiency in future networks. In this paper, we propose a multi-AP multi-user adaptive semantic and bit communication framework for image transmission, where each user can communicate with the access points via either semantic communication (SemCom) or bit communication mode. While the peak mean square error (PMSE) is a key parameter to characterize the difference between the original and corresponding recovered images, this metric has no closed form. We propose a data regression approach to approximate the PMSE. Then, the cost functions for the two types of communication modes are designed, where the delay and energy consumption for image transmission and the PMSE for the recovered image are considered simultaneously. Moreover, the computation delay and energy consumption for semantic feature extraction and recovery are also integrated into the SemCom cost function design. Then, an overall user cost minimization problem is formulated to jointly optimize the communication mode decision, user association, channel selection, power control, and computation resource allocation. To solve the formulated problem, we propose an improved particle swarm optimization based semi-cooperative matching (IPSO-SCM) algorithm, where a semi-cooperative matching (SCM) game is established to determine the communication mode decision, user association, and channel selection and the improved particle swarm optimization algorithm is designed to jointly optimize the power control and computation resource allocation in each step of the constructed SCM game. We further prove the effectiveness, convergence, stability, and extensibility of the proposed IPSO-SCM algorithm. Simulation results are provided to demonstrate the superiority of the proposed scheme.